Compaction of Hyaloclastite from the Active Geothermal System at Krafla Volcano, Iceland. (11th July 2020) - Eggertsson, Guðjón H.; Kendrick, Jackie E.; Weaver, Joshua; Wallace, Paul A.; Utley, James E. P.; Bedford, John D.; Allen, Michael J.; Markússon, Sigurður H.; Worden, Richard H.; Faulkner, Daniel R.; Lavallée, Yan
Abstract : Hyaloclastites commonly form high-quality reservoir rocks in volcanic geothermal provinces. Here, we investigated the effects of confinement due to burial following prolonged accumulation of eruptive products on the physical and mechanical evolution of surficial and subsurface (depths of 70 m, 556 m, and 732 m) hyaloclastites from Krafla volcano, Iceland. Upon loading in a hydrostatic cell, the porosity and permeability of the surficial hyaloclastite decreased linearly with mean effective stress, as pores and cracks closed due to elastic (recoverable) compaction up to 22-24 MPa (equivalent to 1.3 km depth in the reservoir). Beyond this mean effective stress, denoted as P ∗, we observed accelerated porosity and permeability reduction with increasing confinement, as the rock underwent permanent inelastic compaction. In comparison, the porosity and permeability of the subsurface core samples were less sensitive to mean effective stress, decreasing linearly with increasing confinement as the samples compacted elastically within the conditions tested (to 40 MPa). Although the surficial material underwent permanent, destructive compaction, it maintained higher porosity and permeability than the subsurface hyaloclastites throughout the experiments. We constrained the evolution of yield curves of the hyaloclastites, subjected to different effective mean stresses in a triaxial press. Surficial hyaloclastites underwent a brittle-ductile transition at an effective mean stress of 10.5 MPa, and peak strength (differential stress) reached 13 MPa. When loaded to effective mean stresses of 33 and 40 MPa, the rocks compacted, producing new yield curves with a brittle-ductile transition at 12.5 and 19 MPa, respectively, but showed limited strength increase. In comparison, the subsurface samples were found to be much stronger, displaying higher strengths and brittle-ductile transitions at higher effective mean stresses (i.e., 37.5 MPa for 70 m sample, >75 MPa for 556 m, and 68.5 MPa for 732 m) that correspond to their lower porosities and permeabilities. Thus, we conclude that compaction upon burial alone is insufficient to explain the physical and mechanical properties of the subsurface hyaloclastites present in the reservoir at Krafla volcano. Mineralogical alteration, quantified using SEM-EDS, is invoked to explain the further reduction of porosity and increase in strength of the hyaloclastite in the active geothermal system at Krafla.